A global comparison of the nutritive values of forage plants grown in contrasting environments - Lee, Mark A. (Journal of plant research, 2018)
Forage plants are valuable because they maintain wild and domesticated herbivores, and sustain the delivery of meat, milk and other commodities. Forage plants contain different quantities of fibre, lignin, minerals and protein, and vary in the proportion of their tissue that can be digested by herbivores. These nutritive components are important determinants of consumer growth rates, reproductive success and behaviour. A dataset was compiled to quantify variation in forage plant nutritive values within- and between-plant species, and to assess variation between plant functional groups and bioclimatic zones. 1255 geo-located records containing 3774 measurements of nutritive values for 136 forage plant species grown in 30 countries were obtained from published articles. Spatial variability in forage nutritive values indicated that climate modified plant nutritive values. Forage plants grown in arid and equatorial regions generally contained less digestible material than those grown in temperate and tundra regions; containing more fibre and lignin, and less protein. These patterns may reveal why herbivore body sizes, digestion and migration strategies are different in warmer and drier regions. This dataset also revealed the capacity for variation in the nutrition provided by forage plants, which may drive consumer species coexistence. The proportion of the plant tissue that was digestible ranged between species from 2 to 91%. The amount of fibre contained within plant material ranged by 23–90%, protein by 2–36%, lignin by 1–21% and minerals by 2–22%. On average, grasses and tree foliage contained the most fibre, whilst herbaceous legumes contained the most protein and tree foliage contained the most lignin. However, there were individual species within each functional group that were highly nutritious. This dataset may be used to identify forage plant species or mixtures of species from different functional groups with useful nutritional traits which can be cultivated to enhance livestock productivity and inform wild herbivore conservation strategies.